The Association Between Work-Related Rumination and Executive Function Using the Behavior Rating Inventory of Executive Function - Cropley, Mark; Collis, Hannah (Frontiers in Psychology, 2020)
Work-related rumination has been associated with a number of health complaints, however little is known about the underlying mechanisms. Previous work using proxy measures of executive function showed work-related rumination to be negatively associated with executive function. We report two studies that examined the association between work-related rumination and executive function utilizing an ecological valid measure of executive function: the Behavior Rating Inventory of Executive Function (BRIEF-A, Roth, Isquith & Gioia, 2005). In study 1 (N = 63), high, relative to low work-related ruminators, were found to demonstrate lower executive function skills, in eight of the nine subscales of the BRIEF. The aim of study 2 (N = 237) was to identify, the key executive function subscale/s associated with work-related rumination. Controlling for known factors associated with work-related rumination (fatigue and sleep), regression analysis identified the behavioral regulation subscale ‘shift’ as the key predictor within the model. Shift relates to our ability to switch attention, to think about different solutions, and dealing with and accepting change. It was concluded that these findings lend support for future research to develop interventions for enhancing shift ability, as an aid to reduce work-related ruminative thinking.